La motivación escolar y su influencia en el liderazgo educativo en los estudiantes de la UE José María Estrada Coello, Babahoyo 2023 - Miranda de Mora, Irina Stefania (2023)
This article addresses the influence of school motivation on students' educational leadership. The need to allude to this subject is due to the insufficiencies observed in both variables, which affect both personal and institutional achievements. The objective of this work is to evaluate the correlation between school motivation and educational leadership. The methodology applied is mixed, as it integrates quantitative and qualitative aspects. During the study, the survey was used as an empirical method and the Rho Spearman as a statistical correlation test for ordinal variables. As a result, it was obtained that there is a positive association between both variables, therefore, the research hypothesis is assumed and the null hypothesis is discarded.